Bronze Age Lives - Harding, Anthony (2021)
This book provides a personal view of the European Bronze Age by one of its long-standing scholars. It takes the period as a series of "lives": of people, objects, places and societies, as well as of the Bronze Age itself, and provides an overview of research on the period, covering the latest work as well as fundamental studies from the past. While not intended as a systematic overview, it places up-to-date scholarship before a wider public.